The Mediating Effect of Organizational Memory in the Relationship between Organizational Improvisation and Strtegic Myopia in Diversfied Financial Services Companies Listed in the Amman Stock Exchange - Abuzaid, Ahmad Nasser (Jordan Journal of Business Administration, 2024)
The present study examined the mediating effect of organizational memory in the relationship between organizational improvisation and strategic myopia. The study population included the top-management team working in diversified financial services companies. A convenience sample of 130 managers working in twenty-six companies completed an online questionnaire. The present study adopted a descriptive-analytical approach. The author utilized a structural-equation modeling technique to analyze the data and test the hypotheses by using LISREL 8.8 software. The findings reveal that organizational improvisation has a negative effect on temporal and spatial strategic myopia. Additionally, organizational improvisation has a positive impact on organizational memory. Finally, organizational memory partially mediates the relationship between organizational improvisation and temporal and spatial strategic myopia. Based on these findings, companies should encourage using organizational improvisation and organizational memory by managers, as this has been proven to decrease the level of strategic myopia in the company. Similarly, companies should focus on the role of training and the availability of learning opportunities in increasing improvisation abilities.